The king must die - Ashing-Giwa, Kemi (Saga Press, 2025)
"Fen's world is crumbling. Newearth, a once-promising planet gifted by the all-powerful alien Makers, now suffers from failed terraforming, leaving its people on the brink of collapse. Fen has spent her life working as a mercenary bodyguard for a cunning magistrate, entangled in the politics of the empire that shattered her family. But then her fathers--her last remaining tether to hope--are executed by the ruthless Sovereign, who marks Fen for the same fate. With nothing left to lose, Fen escapes with a single map and an old quarterstaff, embarking on a dangerous quest to seek out the last remnants of her parents' rebellion. But the underground insurgents she finds may be even more dangerous than the Sovereign's army. At the center of it all stands Alekhai, the Sovereign's heir--a brutal, power-hungry force of destruction. Though he embodies everything Fen despises, his dangerous plans might be the empire's last chance at survival...or the final push to its doom"--